2010
DOI: 10.1021/jp908985v
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Bovine Serum Albumin with Cationic Single Chain+Nonionic and Cationic Gemini+Nonionic Binary Surfactant Mixtures

Abstract: The interaction of bovine serum albumin (BSA) with cetyltrimethylammonium bromide (CTAB), C(16)C(4)C(16)Br(2), Brij58, and their binary mixtures has been studied using tensiometry, spectrofluorometry, and circular dichroism at physiological pH and 25 degrees C. The tensiometric profiles of CTAB and C(16)C(4)C(16)Br(2) in the presence of BSA exhibit a single break at a lower surfactant concentration termed as C(1) (concentration corresponding to saturation of the interface) compared to their critical micelle co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 67 publications
0
33
0
Order By: Relevance
“…Tripledistilled water (conductance = 1 × 10 −6 mho) was used within seven days of its preparation. Freshly prepared solutions of BSA and surfactants in phosphate buffer of pH 7.4 with triple distilled water [27] were used for each measurement. Different percentages of BSA solution were prepared by dissolving BSA in grams per 100 mL of the solution.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tripledistilled water (conductance = 1 × 10 −6 mho) was used within seven days of its preparation. Freshly prepared solutions of BSA and surfactants in phosphate buffer of pH 7.4 with triple distilled water [27] were used for each measurement. Different percentages of BSA solution were prepared by dissolving BSA in grams per 100 mL of the solution.…”
Section: Methodsmentioning
confidence: 99%
“…Although at 278 nm, both the Trp and Tyr residues are excited, the fluorescence behavior of BSA is mainly due to Trp, and an emission peak appeared at 340 nm [35]. The wavelength of emission maximum and the fluorescence intensity at 340 nm are sensitive to the protein conformation, and hence the intrinsic fluorescence intensity on excitation at 278 nm can be used to examine the protein-surfactant interactions [27]. Fig.…”
Section: Intrinsic Fluorescencementioning
confidence: 99%
“…Most of the literatures about the synergistic effect of the mixed surfactants focused on the mixture of nonionic/ionic surfactants and amphoteric/ionic surfactants [12][13][14][15][16][17][18][19]. It has been reported that the co-adsorption of non-ionic/ionic surfactants or amphoteric/ionic surfactants on the gas/water or oil/water interfaces could improve the interfacial activity significantly by reducing the electrical repulsion between the charged head groups and increasing the interfacial density of the adsorbed molecules [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Owing to their unusual properties (such as high surface activity, much lower cmc, higher solubilization capacity, low Krafft temperature, good wetting, detergency and emulsifying properties), the geminis have been considered the next generation surfactants [1][2][3][4][5][6][7]. Cationic geminis, in particular, have been shown to possess high antifungal, antibacterial and antimicrobial activities [8][9][10][11] and have attracted considerable attention towards their interaction with biologically important ligands [12][13][14][15][16]. Surfactants interact with the membranes causing cell lysis.…”
Section: Introductionmentioning
confidence: 99%
“…Surfactants interact with the membranes causing cell lysis. Cell lysis by the surfactants has fundamental and practical importance mainly in drug targeting or in pharmacology [14][15][16]. Despite very encouraging results of the above interaction studies, the gemini surfactants invariably been used are of m-s-m type (m and s are the number of carbon atoms in the hydrophobic tail and the spacer parts, respectively).…”
Section: Introductionmentioning
confidence: 99%